Slouching Towards Slickville: Sam Slick's Chilly Reception - Smurthwaite, Cynthia (Studies in Canadian Literature, 1997)
Thomas Chandler Haliburton's most famous character, nineteenth-century New Englander and hero of The Clockmaker series Sam Slick, suffers from an poor critical reception that would seem to be the result of personal infamy. In fact, while there is much to legitimately find distasteful in Slick -- his sexism and advocacy of slavery, for instance -- his great international success with contemporary readers suggests that Haliburton's creation has remained, for the most part, a critically misconstrued character. A careful scrutiny of both The Clockmaker series and the critical attention paid it reveals a Sam Slick to whom the critics have been oddly oblivious. While Slick's character is inextricable from his satiric function in Haliburton's series, a closer reading helps in the recognition of Slick's more admirable traits, such as an impressive self-knowledge and a very realistic sense of dialect, which had hitherto lain unobserved amongst his faults.